Supporting married, cohabiting and divorced adolescents: insights from comparative research - van der Gaag, N (Young Lives, 2020)
This is the 2nd policy brief from the Young Marriage and Parenthood Study (YMAPS), a qualitative research study carried out between 2017 and 2020 by Young Lives and Child Frontiers in Ethiopia, India (Andhra Pradesh and Telangana states), Peru, and Zambia. It highlights findings from the study and proposes policy recommendations to ensure that young people experiencing marriage, co-habitation and parenthood feel safe and cared for in their relationships; live a dignified life despite poverty; are able to return to, or finish their education and access training; and most importantly, to ensure that their own children go to school in order to give them a better future. Understanding, supporting and listening to this generation of adolescents who have married or cohabited and become parents in a critical step in breaking the cycle of young marraige for the next generation and achieving the UN Sustainable Development Goals by 2030.